How Ambonese Read: Challenges and Opportunities to Preserve Maluku Folklore and Culture - Rijoly, Helena M. (Pattimura University, 2022)
Preserving culture can be done through the folklore that are passed down from generation to generation. The main aim of this survey is to see the challenges and opportunity for Maluku Folklore preservation. This research provides an insight on the students’ reading habit and preference, the availability of Maluku Folklore, and students’ perception on Maluku folklore. The data collected 248 responses through an online survey. The result highlighted several interesting information; 1) Despite the result show respondents perceived reading as their hobby, their preference activity shows that in their free time books are not the first choice and the culture of bedtime stories and/or being read to by parents are an uncommon practice. 2) Students rarely read Maluku Folklore unless it is an assignment from school. 3) Students believed that Maluku Folklore is not as popular and available compared to folklore from other parts of Indonesia. 4) Maluku Folklore is not readily available for students to find and consume. 5) Students prefer to read on digital and online platforms compared to the printed ones. 6) Opportunities for preservation can be done by embracing the technology and internet to tapped in to the current young people reading preferences and habit.